FREQUENCY OF COMPLETE HEALING, INCONTINENCE AND RECURRENCE IN HIGH VARIETY OF ANAL FISTULA AFTER SETON TREATMENT (The Research of Medical Science Review, 2025)
Objective: To evaluate the clinical outcomes, recurrence rates, and factors influencing the prognosis of patients undergoing surgical treatment for anal fistula, with a focus on patient characteristics, treatment modalities, and post-operative complications. Place and Duration of Study: Conducted at Department of Surgery, Nishter Hospital, Multan, Pakistan, for one year after approval of synopsis. Study Design: A prospective observational study. Methodology: All 70 patients with a high variety anal fistula underwent seton treatment. Demographic and clinical variables with details of treatment were noted. Statistical analyses, unadjusted and adjusted odds ratios with 95% confidence intervals. T-tests or ANOVA were used to analyze continuous variables and logistic regression was used for categorical variables. Statistical significance was defined as p-values <0.05. Results: Participants had mean age of 42.6 ± 10.8 years (40% were 31-45 years, 30% were 18-30 years, 22% were 46-60 years and 8% were above 60 years) 85.7% were male and 14.3% were female. Forty percentage of simple, 42.9% complex and 17.1% recurrent fistulas were detected. Recurrences occurred in 18.6% of cases. Complete healing at three months was observed in 61.4%, at three to six months in 28.6% and at more than six months in 10%. Almost 15.7% developed posttreatment infection and 27.1% faecal incontinence. Recurrence was significantly related to the type of fistula (p value: 0.023, OR: 3.11, 95% CI: 1.18-8.21). Faecal incontinence showed a correlation with sphincter damage (p < 0.001), while compliance with follow-up emerged as a significant risk factor for complete healing (p = 0.009, OR = 2.89, 95% CI: 1.32-6.31). Conclusion: Surgical outcomes of anal fistula are driven by a number of factors related to the patient and the underlying disease. Improving care after surgery and helping to ensure that patients take their medication as prescribed may increase the chances of a good clinical outcome and lower the rate of recurrence.